(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The problem of invasive plant species is becoming more popular all over the world. The peculiarities of alien plant species is also growing in Latvia every year. Invasive species are the serious problem for natural ecosystem and species protection, in traditional landscape visual conservation as well it shows noticeable economical reducing in farming. Existing flora and its structure was as appearing in approximately 10 000-15 000 years after the last examining. It is still developing, quantitative and qualitative plant changes continue to grow in flora. That has an influence on natural narrowing, distribution and species changes. In Latvia, as well in such city as Daugavpils, such questions as alien plant growing were examined only in some fragments. An alien plant growing was analyzed. The following facts are found the biggest plant concentration is noticed in dry and sunny places well near the artificial plant areas.